Care of traditional patients in the campaign against COVID-19: casualties of friendly fire - Mukta Chandra Srivastava (Greater Baltimore Medical Center, 2020)
In response to the COVID-19 pandemic, hospitals have adopted protocols geared to optimize the care of patients with COVID-19, while mitigating risk of exposure to other patients and to health care workers. These modifications can have un-intended consequences and impact the care of non-COVID patients. In the campaign against COVID-19, we must remain vigilant that patients with traditional disease processes also receive thoughtful and coordinated care.